1998
DOI: 10.1016/s0005-2736(98)00082-0
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome membrane permeability to anions

Abstract: The permeability of rat liver lysosomes to some inorganic and aliphatic organic anions was investigated, using an osmotic-protection methodology. Lysosomes were incubated at 25 degreesC in 250 mOsm solutions of potassium salts of the anions, in the presence of valinomycin, and the latency of lysosomal hexosaminidase measured at intervals. Lysosomes suspended in 250 mM sucrose at 25 degreesC were stable for up to 4 h. When suspended in 250 mOsm solutions of potassium salts of inorganic acids, latency was lost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Third, AQP6 is not inhibited by known anion channel inhibitors such as DIDS, 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), niflumic acid, and diphenylamine-2-carboxylic acid (DPC) (3). Interestingly, the permeability sequence is identical to that of lysosomal membranes (25). The acidic pH within the interior of lysosomes is generated and maintained FIG.…”
Section: Discussionmentioning
confidence: 86%
“…Third, AQP6 is not inhibited by known anion channel inhibitors such as DIDS, 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB), niflumic acid, and diphenylamine-2-carboxylic acid (DPC) (3). Interestingly, the permeability sequence is identical to that of lysosomal membranes (25). The acidic pH within the interior of lysosomes is generated and maintained FIG.…”
Section: Discussionmentioning
confidence: 86%
“…18 Still, negatively charged functional groups such as carboxylates are known to hinder diffusion through lipid bilayer membranes. 24, 25 We anticipated that replacing the carboxylic acid with a functional group surrogate would modulate the physicochemical properties of the inhibitor and might enhance its ability to permeate mycobacteria. We identified the N -acylsulfonamide functionality as a promising candidate, as it previously has been employed as a carboxylic acid bioisostere 26 and can successfully mimic phosphate groups.…”
mentioning
confidence: 99%
“…The observation that the carboxylate moiety of the 2-aminothiazole inhibitors is crucial for activity against UGM suggests that it mimics the pyrophosphate group . Still, negatively charged functional groups such as carboxylates are known to hinder diffusion through lipid bilayer membranes. , We anticipated that replacing the carboxylic acid with a functional group surrogate would modulate the physicochemical properties of the inhibitor and might enhance its ability to permeate mycobacteria. We identified the N -acylsulfonamide functionality as a promising candidate that was previously employed as a carboxylic acid bioisostere and can successfully mimic phosphate groups. , N -Acylsulfonamides have lower p K a values compared to those of carboxylic acids and are expected to be ionized under physiological conditions .…”
mentioning
confidence: 99%
“…3) showed that there was a requirement, which could not be fulfilled by gluconate, but there was no stringent requirement for chloride. The activity with nitrate may be explicable by diffusion of this anion through the membrane (37); sulfate, in contrast, is less membrane-permeable than chloride (37). Therefore, the acidocalcisome membrane may have an anion channel generally permeable to small anions.…”
mentioning
confidence: 99%